Binocular vision emerges from the coordinated development of orbit convergence, eye orientation, and high-acuity retinal specializations - Alfonso Deichler; Macarena Ruiz-Flores; Natalia I. Márquez; Cristian Morales; Luciana López-Jury; Tomas Vega-Zuniga; Jorge Mpodozis; Macarena Faunes; Gonzalo J. Marín (Proceedings of the National Academy of Sciences, 2026)
Binocular vision requires both eyes to be aligned such that their visual fields overlap. A long-standing premise derived from comparative studies is that the orientation of the orbits determines eye position, and thereby the extension of this overlap, the binocular field. In addition, to produce an accurate neural representation, the binocular field must integrate with the position of retinal high-acuity areas and with the extent of uncrossed retinal projections. It remains unknown, however, whether the binocular field is already formed at the time of eye-opening, as well as when and how it integrates with neuroanatomical visual traits during development. Using the diurnal rodent Octodon degus , a suitable animal model for visual neuroscience, we combined CT-based 3D cranial reconstructions, quantitative measurements of visual-field geometry, whole-mount retinal topography, neural tracing of retinal projections, and behavioral assays to reconstruct the postnatal assembly of the binocular visual system. We show that orbital and ocular orientations shift substantially after birth, broadening the dorsal binocular field; that retinal ganglion cell distributions sharpen into a horizontal visual streak and a defined area centralis ; and that ipsilateral projections to the superior colliculus mature in parallel to binocular expansion. These changes coincide with the emergence of binocular-dependent behaviors such as depth discrimination and looming-evoked escape responses. Together, our findings demonstrate that binocular vision emerges through the coordinated alignment of multiple developmental processes across levels of organization.